2020
DOI: 10.3389/fneur.2019.01404
|View full text |Cite
|
Sign up to set email alerts
|

An Up-to-Date Overview of the Complexity of Genotype-Phenotype Relationships in Myotonic Channelopathies

Abstract: Myotonic disorders are inherited neuromuscular diseases divided into dystrophic myotonias and non-dystrophic myotonias (NDM). The latter is a group of dominant or recessive diseases caused by mutations in genes encoding ion channels that participate in the generation and control of the skeletal muscle action potential. Their altered function causes hyperexcitability of the muscle membrane, thereby triggering myotonia, the main sign in NDM. Mutations in the genes encoding voltage-gated Cl − and Na + channels (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 136 publications
0
35
0
7
Order By: Relevance
“…Other researchers have also reported a few patients with the same genes mutated (Table 3) [15][16][17][18]. These patients showed an atypical phenotype, suggesting that concomitant mutations may act synergistically to influence the phenotype [19]. However, the symptoms of the two diseases so far seemed independent of each other in VI: 3.…”
Section: Discussionmentioning
confidence: 93%
“…Other researchers have also reported a few patients with the same genes mutated (Table 3) [15][16][17][18]. These patients showed an atypical phenotype, suggesting that concomitant mutations may act synergistically to influence the phenotype [19]. However, the symptoms of the two diseases so far seemed independent of each other in VI: 3.…”
Section: Discussionmentioning
confidence: 93%
“…It has been widely recognized that NDMs are not easy to distinguish, clinically or genetically, mainly due to the phenotypic overlap among these diseases and the great number of mutations with different effects, inheritance patterns and associated phenotypes [ 3 ]. In this study, we identified four genetic mutations in the CLCN1 and SCN4A genes in three Costa Rican families and described their clinical and electrophysiological findings.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, proband NDM16, who is compound heterozygous carrying these two mutations, was, in fact, diagnosed with RMC, indicating that neither allele can give rise to a functional ClC-1 channel. Similarly, proband NDM15, who resulted homozygous for the W322* mutation, should have been diagnosed with Becker’s type myotonia, but instead, he was diagnosed with severe DMC [ 17 ], indicating that the W322* mutation might be another example of CLCN1 mutations associated with both phenotypes and inheritance patterns [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myotonia was a genetically and heterogeneous disease due to the electrical hyper-excitability of muscle fibers (Morales and Pusch 2019). Non-dystrophic myotonia (NDM), a common type of myotonia, had been estimated to be approximately 1 in 100,000 according to a recent report (Snyder et al 2015).…”
Section: Introductionmentioning
confidence: 99%